Pemberian Larutan Garam terhadap Penurunan Kadar Formalin pada Tahu - Rosnita Sebayang; Kesatria Bayu Kencana; Ines Samosir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The study aimed to identify the effect of formalin in tofu on boiling in a solution of kitchen salt by cooking with several temperatures. This research method is a laboratory experiment to determine a decrease in formalin in white tofu added with a salt solution concentration of 1%, 2%, 3% by boiling for 10, 15, 20 minutes. Research results based on ANOVA test analysis, there is the effect of heating to boiling (1000 C), in a 1% salt solution p-value = 0,000. In conclusion, there is an effect of giving a salt solution to decrease formalin levels in tofu. Keywords: Formalin, Salt, Tofu